A Link between Mitochondrial Dysregulation and Idiopathic Autism Spectrum Disorder (ASD): Alterations in Mitochondrial Respiratory Capacity and Membrane Potential - Hazirah Hassan; Fazaine Zakaria; Suzana Makpol; Norwahidah Abdul Karim (Current Issues in Molecular Biology, 2021)
Autism spectrum disorder (ASD) is a neurological disorder triggered by various factors through complex mechanisms. Research has been done to elucidate the potential etiologic mechanisms in ASD, but no single cause has been confirmed. The involvement of oxidative stress is correlated with ASD and possibly affects mitochondrial function. This study aimed to elucidate the link between mitochondrial dysregulation and idiopathic ASD by focusing on mitochondrial respiratory capacity and membrane potential. Our findings showed that mitochondrial function in the energy metabolism pathway was significantly dysregulated in a lymphoblastoid cell line (LCL) derived from an autistic child (ALCL). Respiratory capacities of oxidative phosphorylation (OXPHOS), electron transfer of the Complex I and Complex II linked pathways, membrane potential, and Complex IV activity of the ALCL were analyzed and compared with control cell lines derived from a developmentally normal non-autistic sibling (NALCL). All experiments were performed using high-resolution respirometry. Respiratory capacities of OXPHOS, electron transfer of the Complex I- and Complex II-linked pathways, and Complex IV activity of the ALCL were significantly higher compared to healthy controls. Mitochondrial membrane potential was also significantly higher, measured in the Complex II-linked pathway during LEAK respiration and OXPHOS. These results indicate the abnormalities in mitochondrial respiratory control linking mitochondrial function with autism. Correlating mitochondrial dysfunction and autism is important for a better understanding of ASD pathogenesis in order to produce effective interventions.